2016
DOI: 10.1038/srep36137
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in colonization of gut microbiota from a man with short-term vegetarian and inulin-supplemented diet in germ-free mice

Abstract: Gnotobiotic mouse model is generally used to evaluate the efficacy of gut microbiota. Sex differences of gut microbiota are acknowledged, yet the effect of recipient’s gender on the bacterial colonization remains unclear. Here we inoculated male and female germ-free C57BL/6J mice with fecal bacteria from a man with short-term vegetarian and inulin-supplemented diet. We sequenced bacterial 16S rRNA genes V3-V4 region from donor’s feces and recipient’s colonic content. Shannon diversity index showed female recip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 48 publications
6
39
0
Order By: Relevance
“…Future in vivo studies can clarify the potential differential effect on the gut microbiota of the two preparations. Importantly, in this study, similarly to previous observations, we observed gender dependent differential responses to diet partly attributed to hormonal effects 78,79 .…”
Section: Translatability To Human Nutritionsupporting
confidence: 91%
“…Future in vivo studies can clarify the potential differential effect on the gut microbiota of the two preparations. Importantly, in this study, similarly to previous observations, we observed gender dependent differential responses to diet partly attributed to hormonal effects 78,79 .…”
Section: Translatability To Human Nutritionsupporting
confidence: 91%
“…In the pubertal subjects, it was found that the abundance of genus Adlercreutzia, Dorea, Clostridium and Parabacteroides associated with the level of testosterone. A mouse model study showed that after inoculating male and female germ-free C57BL/6J mice with fecal bacteria from a man with short-term vegetarian and inulin-supplemented diet, Clostridium and Dorea were over-represented in females (25). Furthermore, Shin JH (26) reported that the abundance of Dorea correlated signi cantly with testosterone levels in men, a nding consistent with the results of our study.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in humans and mice suggest that differences in endocrine and immune systems between sexes induce different gut microbiota profiles in males and females (Fransen et al, 2017). Studies have demonstrated sexual dimorphism in several aspects of gut microbiota, including their composition (Dominianni et al, 2015;Mueller et al, 2006;Li et al, 2008), their changes in response to factors such as diet (Bolnick et al, 2014;Karunasena, McMahon, Chang, & Brashears, 2014) and their diversity, structure and individual phylotype during the colonization in germ-free mice (Wang et al, 2016). Females have consistently shown lower abundance of Bacteroidetes in their microbiota, a group of bacteria with beneficial effects in metabolism (Dominianni et al, 2015;Mueller et al, 2006).…”
Section: Discussionmentioning
confidence: 99%